EGCG Inhibits Proliferation and Induces Apoptosis Through Downregulation of SIRT1 in Nasopharyngeal Carcinoma Cells - Jiang, Shisheng; Huang, Chaoming; Zheng, Guodong; Yi, Wei; Wu, Bo; Tang, Junyuan; Liu, Xiawen; Huang, Biyun; Wu, Dan; Yan, Tingdong; Li, Mingxi; Wan, Chunpeng; et al. (Frontiers in Nutrition, 2022)
Epigallocatechin-3-gallate (EGCG), a frequently studied catechin in green tea, has been shown involved in anti-proliferation and apoptosis of human nasopharyngeal carcinoma (NPC) cells. However, the underlying molecular mechanism of the apoptotic effects of EGCG has not been fully investigated. Recent literature emphasized the importance of Sirtuin 1 (SIRT1), an NAD+-dependent protein deacetylase, in regulating cellular stress responses, survival, and organismal lifespan. Herein, the study showed that EGCG could significantly inhibit cell proliferation and promote apoptosis of 2 NPC (CNE-2 and 5-8F) cell lines. Moreover, it was also found that SIRT1 is down-regulated by EGCG, and the SIRT1-p53 signaling pathway participates in the effects of EGCG on CNE-2 and 5-8 F cells. Taken together, the findings of the present study provided evidence that EGCG could inhibit the growth of NPC cell lines and is linked with the inhibition of the SIRT1-p53 signaling pathway, suggesting the therapeutic potential of EGCG in human NPC.